Keratolytic Winter Erythema: An Update - Michèle Ramsay; Thandiswa Ngcungcu; Wayne Grayson (MDPI AG, 2019)
Keratolytic winter erythema (KWE) is a rare autosomal dominant keratoderma affecting primarily the palms and soles, manifesting with recurrent waves of erythema followed by epidermal peeling. The condition is so named in view of its anecdotal worsening during the winter months. It is highly penetrant but shows considerable individual clinical variability, waning and reappearing throughout the life course. Histologically, early established lesions of KWE manifest with degenerative changes involving the Malpighian layer, with associated absence of the stratum granulosum. The damaged zone undergoes parakeratotic transformation and subsequent centrifugal ejection. Thick peeling occurs when the stratum corneum eventually separates off as a result of a keratolytic split occurring above, through or below the parakeratotic zone. Reconstitution of the stratum granulosum ensues. KWE is caused by a duplication of an intergenic enhancer element upstream of the cathepsin B gene on chromosome 8. This leads to the upregulation of cathepsin B in the stratum granulosum and subsequent peeling of the epidermis as the end result. With elucidation of the molecular pathology of KWE, new therapeutic approaches to KWE may be considered.